2012
DOI: 10.1002/cjg2.1751
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Infrasonic Waves Before a Small Earthquake in Beijing

Abstract: Anomalous infrasound waves were recorded at five infrasonic monitoring stations four days before a small earthquake which happened in Beijing on 12 October 2011. Waveforms of these five signals are consistent, which are N-shaped impulse waves with same duration of about one hour. Using the Wigner-Ville distribution method, time-frequency analysis of the signals suggests that waves' energies concentrate mainly below the frequency of 0.025 Hz. Correlation coefficients between two signals are all up to about 0.8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The only one instance found is that Yang Yichun positioned the Lushan earthquake and Pakistan earthquake happened in 2013. There was some lag between the positioning result and the epicenter [3].…”
Section: Introductionmentioning
confidence: 98%
“…The only one instance found is that Yang Yichun positioned the Lushan earthquake and Pakistan earthquake happened in 2013. There was some lag between the positioning result and the epicenter [3].…”
Section: Introductionmentioning
confidence: 98%
“…Because of their low frequency, infrasonic waves have strong penetration, small attenuation in air to travel in the atmosphere for long distance. 2004;Ulivieri et al 2011), earthquakes (Le Pichon et al 2005Lin and Yang 2010;Lü et al 2012;Yang et al 2014), nuclear explosions (Christie et al 2001;Krasnov and Drobzheva 2005;Qin et al 2013), and atmospheric environment studies (Brachet et al 2009;Drob et al 2009;Le Pichon et al 2010). With its research into a maturity period, infrasonic sound monitoring found applications in the investigation of volcano eruptions (Johnson 2003;Matoza et al 2009;Ripepe et al 2010), avalanches (Scott et al 2006(Scott et al , 2007Comey and Mendenhall.…”
mentioning
confidence: 99%
“…The infrasonic signals occurred after earthquakes are characterized by(Mutschlecner and Whitaker 2005;Lü et al 2012): 1) amplitudes from 0.01 Pa to several Pa; 2) wide frequency band, usually in 0.005~10 Hz; 3) very short time duration, about several seconds. 2005; Lin and Yang 2010; Xia et al 2011): 1) the maximum amplitude is less than 10Pa; 2) low frequency, narrow frequency band and energy concentrates below 0.25 Hz; 3) usually crops up, and lasts long time, about thousands of seconds; 4)The waveform is of two types, i. e. sine wave and pulse wave.…”
mentioning
confidence: 99%